Exploration of Dimethylzinc‐Mediated Radical Reactions. Issue 5 (17th July 2015) - Yamada, Ken‐ichi; Tomioka, Kiyoshi
Abstract: In this account, our studies on radical reactions that are promoted by dimethylzinc and air are described. Advantages of this reagent and differences from conventional radical initiators, such as triethylborane, are discussed. Abstract : Our studies on radical reactions that are promoted by dimethylzinc and air are described. Advantages of this reagent and differences from conventional radical initiators, such as triethylborane, are discussed.